2019
DOI: 10.15405/epsbs.2019.04.12
|View full text |Cite
|
Sign up to set email alerts
|

Attributes And Sectoral Characteristics Of Innovative Cluster

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Moreover, Napolskikh et al (2019) examine the characteristics and contradictions in the development of clusters and the main types of innovation clusters as the main form of integration of high-tech industries at the regional level and throughout the territory. The analysis of the results of the study revealed that the development of theoretical and methodological approaches for the spatial modeling of the innovation cluster is based on its examination as a complex meso economic system with a specific structure of the organizational hierarchy and horizontal network interactions, as well as their own mechanisms.…”
Section: Various Domains Of Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Napolskikh et al (2019) examine the characteristics and contradictions in the development of clusters and the main types of innovation clusters as the main form of integration of high-tech industries at the regional level and throughout the territory. The analysis of the results of the study revealed that the development of theoretical and methodological approaches for the spatial modeling of the innovation cluster is based on its examination as a complex meso economic system with a specific structure of the organizational hierarchy and horizontal network interactions, as well as their own mechanisms.…”
Section: Various Domains Of Clustersmentioning
confidence: 99%
“…The analysis and study of all the results and conclusions of previous research and studies leads us to some observations. Firstly, Napolskikh et al (2019) state in their study that the development of theoretical and methodological approaches for the spatial modeling of the innovation cluster is based on considering it as a complex meso economic system with a specific structure of organizational hierarchy and horizontal network interactions, as well as their own mechanisms. Also, companies that are members of an innovation cluster can compete effectively in global technology and innovative markets only if the clustering processes of the economic system are provided with appropriate theoretical and methodological support.…”
Section: Various Domains Of Clustersmentioning
confidence: 99%